2018
DOI: 10.1021/acssuschemeng.8b03204
|View full text |Cite
|
Sign up to set email alerts
|

High Yield, Low-Waste Synthesis of a Family of Pyridyl and Imidazolyl-Substituted Schiff Base Linker Ligands

Abstract: Solid-state synthesis (S 3 ) is an attractive approach to organic synthesis as in principle it offers minimal solvent waste and high yield. However, many functional groups are ill-suited for S 3 reactions, which tend to only proceed when substrates are aligned in the solid-state according to the topochemical principle. The aim of this work is to use high yield, low-waste synthetic methods to develop a library of novel Schiff bases that can be utilized as linker ligands to prepare coordination networks. Herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 95 publications
1
23
0
Order By: Relevance
“…Anhydrous forms of 5 – 7 were observed to transform to hydrated forms of 5 – 7 following aqueous slurry and exposure to humidity. Anhydrous samples of 4 – 11 were also subjected to aqueous SDG. ,, Hydrated forms of 5 – 7 were isolated from the SDG experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anhydrous forms of 5 – 7 were observed to transform to hydrated forms of 5 – 7 following aqueous slurry and exposure to humidity. Anhydrous samples of 4 – 11 were also subjected to aqueous SDG. ,, Hydrated forms of 5 – 7 were isolated from the SDG experiments.…”
Section: Resultsmentioning
confidence: 99%
“…1 – 11 were prepared following procedures reported in the literature. 5 – 9 were prepared by a facile synthetic strategy, co-crystal controlled solid-state synthesis, developed by us . Single crystals of 7· 4H 2 O and 10 were isolated by slow evaporation of a saturated solution of either 7 or 10 in CHCl 3 /MeOH (1:1 v/v) over 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…1a). 43,44 A 1 : 1 ground mixture of 1,8-NA and 3APy formed an intermediate via SDG when using 120 μL of EtOH. The imide was obtained by heating the intermediate at 185°C for 5 h, affording 5 in 93% yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this contribution, we report the solid-state synthesis 2-( pyridin-3-yl)-benzo[de]isoquinoline-1,3(2H)-dione, 5, and its use as a Werner complex ligand. The formation of imides from Cocrystal Controlled Solid-State Synthesis (C 3 S 3 ) has been previously exploited by our group as a mechanochemical approach to prepare ligands [43][44][45] and typically involves solventdrop grinding (SDG) [46][47][48] followed by heating. Advantages of C 3 S 3 include the following: (i) little solvent is required, especially compared to solution-based synthesis methods; (ii) yields are typically high, often approaching quantitative; (iii) new condensation products can be readily accessible from simple organic building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that imidazole-based compounds have good biological activities such as insecticidal, bactericidal, herbicidal, antiviral, anticancer etc. [4][5][6].…”
Section: Commentmentioning
confidence: 99%